Changes in the Metabolism of Fucose-Containing Biopolymers in Rat Gastrointestinal Tissues under Immobilization Stress - Oksuzyan, A.V.; Butolin, E.G.; Bryzgalina, A.A. (Biomedical Chemistry: Research and Methods, 2024)
The features of fucoglycoprotein metabolism in blood serum and tissues of gastrointestinal tract of rats in the dynamics of experimental stress on 21, 35, 60, 90 days of observation were considered. In blood serum and in homogenates of liver, stomach and small intestine of immobilized rats multidirectional changes in the level of fucose and fucosidase activity were observed. They are manifested by a decrease in the amount of total fucose in blood serum and liver of rats against the background of low activity of the enzyme degrading fucoglycoproteins. The same changes were detected in the tissues of the gastric and small intestine (except on day 35 of the experiment, when the growth of fucose and fucosidase was visualized), which may indicate a change in metabolism toward anabolism. These changes correlate with an increase in the concentration of corticosterone in the blood serum of the rats.